About one of the unique finds of the late pre-Scythian period from the Koban necropolis - Makhortykh, S.; Grömer, K.; Tiefengraber, G. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The Koban сulture is one of the most prominent cultural phenomena in the Caucasus region. Its materials are kept in many European museums and are the subject of interest of a wide scientific community. The Koban assemblages stored in the Vienna Natural History Museum are among the most significant museum collections of the Caucasian antiquities in Europe. This collection was acquired in the 19th century by Franz Heger, director of the anthropological and ethnographical department of the Museum, and includes more than 30 representative burial complexes with highly informative artefacts of the eponymous site Koban necropolis. These data are not yet known to researchers. The assemblages from Vienna are unique, because they belonged to the elite members of the society, whose burials included valuable grave goods and burial costume elements. This makes the collection in Vienna a key site to be considered for research questions related to the culture and history of the Central Caucasus between the 10th and 5th centuries BC. The following article is devoted to the analysis of one of the most interesting finds from the Koban cemetery — a bronze pin decorated with the cast figure of a horseman discovered in the burial No. 1 (1884).
Қобан қорымының ежелгі сақтарға дейінгі кезеңінің бірегей олжасы туралы
Об одной уникальной находке позднейшего предскифского периода из Кобанского некрополя
Keywords: Vienna Natural History Museum; Caucasian collection; Koban сulture; Koban cemetery; graves; 8th century BC; metalworking; bronze pin; horseman; bow